Contemporary Evidence and Practice on Right Heart Catheterization in Patients with Acute or Chronic Heart Failure - Lina Manzi; Luca Sperandeo; Imma Forzano; Domenico Simone Castiello; Domenico Florimonte; Roberta Paolillo; Ciro Santoro; Costantino Mancusi; Luigi Di Serafino; Giovanni Esposito; Giuseppe Gargiulo (Diagnostics, 2024)
Heart failure (HF) has a global prevalence of 1–2%, and the incidence around the world is growing. The prevalence increases with age, from around 1% for those aged <55 years to >10% for those aged 70 years or over. Based on studies in hospitalized patients, about 50% of patients have heart failure with reduced ejection fraction (HFrEF), and 50% have heart failure with preserved ejection fraction (HFpEF). HF is associated with high morbidity and mortality, and HF-related hospitalizations are common, costly, and impact both quality of life and prognosis. More than 5–10% of patients deteriorate into advanced HF (AdHF) with worse outcomes, up to cardiogenic shock (CS) condition. Right heart catheterization (RHC) is essential to assess hemodynamics in the diagnosis and care of patients with HF. The aim of this article is to review the evidence on RHC in various clinical scenarios of patients with HF.